THE PROVISION ECOLOGICAL FAVOURABLE ENERGY, NOT REQUIRING RAW MATERIAL - Mashkov, V.V (European Scientific Journal, ESJ, 2014)
Chaos is formed from uncountable ensemble of( Individual Event. The Statistical Physics and discrete mathematics do not provide most full study characteristic natures and, as effect, do not allow the mankind to find and create ecological clean, very much cheap sources to energy. The Physics microworld, physics whirlwind phenomenas must be considered with use: 1) as acceptance and result Statistical Physicists and Thermodynamics, giving immeasurable effect of the generalizations, 2) so and with use Physicists Individual processes in microworld and macroworld, considering events in microworld and macroworld with position real, not abstract essence of the material world. Decision of the problems of the provision mankind ecological clean and cheap energy can be provided by creation of Whirlwind ElektroField Electric Station (WEFES). In article appears, as in nature occurs natural transition a material in energy under Itself-free disinteration uranium element and at whirlwind phenomenas type hurricane "Katrin". The Scientist, copying nature, can create the whirlwind energy installation and get the additional energy, using fundamental characteristic of the nature to translate the material in energy.